(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article emphasizes that the creation of favorable conditions for increasing the socio-political activity of women in the country, ensuring their legal interests, realization of their abilities and potential in various fields is an important priority of public policy, strengthening the role of society Scientific conclusions have been drawn on the fact that significant work has been done to protect their rights and legitimate interests.